Trade finance evolution: a comparative study of regulatory reforms in factoring policies for SMEs in India and China - Kashyap, Amit Kumar; Lunagariya, Simran (Department of Government Studies, Universitas Muhammadiyah Makassar, 2023)
This paper evaluates the effectiveness of the Factoring Regulation (Amendment) Bill 2021 in stabilizing the economic situation of micro, small, and medium-sized enterprises (MSMEs) in India using doctrinal research methods and comparative study. It compared the factoring regulations of India and China. The authors analyse the ramifications of the recent amendments to the Factoring law via a comprehensive literature review, legal frameworks, and comparative analysis of India and China. This study seeks to cast light on the potential of the Factoring Law in addressing the financial challenges encountered by SMEs in India. The findings provide policymakers, stakeholders, and researchers with vital insights into the regulatory framework's effectiveness and potential improvement areas. The research concluded that factoring is an important worldwide trade financing tool for economic development and financial inclusion since it promotes entrepreneurship, private enterprise, and supply chain finance. In order to raise its standing, India may consider adopting features from the Chinese Civil Code, setting regulations for factoring rights transfer, and prioritising creditor interests.